Fatigue Test on Heavy Haul Railway Tunnel Bottom Structure With Base Cavity - Liu, Cong; Wu, Bo; Li, Rui; Wang, Feng; Tang, Qianlong (Frontiers in Earth Science, 2022)
Base cavity will deteriorate the bearing capacity of the tunnel bottom structure, and will also play a noteworthy impact on its fatigue performance. In order to study the fatigue performance and cumulative damage of tunnel bottom structure, a series of bending fatigue tests are conducted by reference to a heavy haul railway tunnel with base cavity. Through the tests, fatigue evolution characteristics of tunnel bottom structure with cavity are obtained, then based on the expression of S-N curves, a non-linear fatigue cumulative damage model is therefore proposed, the deflection evolution and cumulative damage evolution can be divided into three stages and characterized with a “s-shaped” curve. The tests results reveal that, the damage of the tunnel bottom structure develops rapidly when a cavity exists in the base rock, the fatigue failure is easier to occur, and the fatigue life of specimens decreases with the increase of the stress level and cavity width.